Does art expertise facilitate distancing?. (29th November 2017) - Leder, Helmut; Schwarz, Norbert
Abstract: With respect to the Distancing-Embracing model, we discuss whether experts with well-developed and highly accessible schemata that lend themselves to distancing have initial affective reactions similar to those of novices, who lack access to well-developed distancing mechanisms, and whether differences between experts' and novices' responses are apparent only after distancing mechanisms have had a chance to do their work. We revisit findings from Leder et al. (2014) and discuss the role of mixed emotions and fluency.